The Dok‐3/Grb2 adaptor module promotes inducible association of the lipid phosphatase SHIP with the BCR in a coreceptor‐independent manner. Issue 11 (14th September 2016) - Manno, Birgit; Oellerich, Thomas; Schnyder, Tim; Corso, Jasmin; Lösing, Marion; Neumann, Konstantin; Urlaub, Henning; Batista, Facundo D.; Engelke, Michael; Wienands, Jürgen
Abstract : The inositol phosphatase SHIP limits antigen‐mediated B cell activation to prevent autoimmune phenomena. SHIP action is believed to require BCR coreceptors such as FcγRIIb. Manno et al. now show that the BCR can engage SHIP directly by virtue of Igα/Igβ ITAMs and the Dok3/Grb2 protein adaptor module. The BCR‐autonomous feed‐back inhibition can balance B cell activation independently of additional signal input. Abstract : The SH2 domain‐containing inositol 5'‐phosphatase (SHIP) plays a key role in preventing autoimmune phenomena by limiting antigen‐mediated B cell activation. SHIP function is thought to require the dual engagement of the BCR and negative regulatory coreceptors as only the latter appear capable of recruiting SHIP from the cytosol to the plasma membrane by the virtue of phosphorylated immunoreceptor tyrosine‐based inhibitory motifs. Here, we demonstrate a coreceptor‐independent membrane recruitment and function of SHIP in B cells. In the absence of coreceptor ligation, SHIP translocates to sites of BCR activation through a concerted action of the protein adaptor unit Dok‐3/Grb2 and phosphorylated BCR signaling components. Our data reveal auto‐inhibitory SHIP activation by the activated BCR and suggest an unexpected negative‐regulatory capacity of immunoreceptor tyrosine‐based activation motifs in Igα and Igβ.